Concentration, uptake and use efficiency of N, P and K in Panicum maximum jacq. cv. Tobiatã under water stress - Filho, Moacyr Bernardino Dias; Corsi, Moacyr; Cusato, Sueli (Pesquisa Agropecuaria Brasileira, 1992)
The concentration, uptake and element use efficiency of N, P and K in Panicum maximum cv. Tobiatã, under different conditions of soil moisture were determined in a greenhouse experiment by subjecting the plants to three soil moisture regimes: 1) 45% (field capacity), 2) 29%, and 3) varying from 37% to 27% of soil water content. The evaluations were made at 7, 14, 21 and 28 days after the imposition of the soil moisture condition. The basic treatment design was a factorial combination of soil water status x period of evaluation. A complete randomized design with there replications was used. Moisture deficit generally increased (N and K) or had no significant effect (P) on nutrient concentration. Uptake of K and N was relatively less affected by water stress than P uptake, which was negatively influenced. The nutrient use efficiency was maximum for P, irrespective of the water regime. Water estress generally had a deleterious effect on the nutrient use efficiency.